Correlation of hemostasis system indices with lipid peroxidation markers in pregnant women with preeclampsia - Шамелашвілі, К. Л.; Лоскутова, Т. О.; Штеменко, Н. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
We have studied the system of hemostasis in pregnant women with preeclampsia. Platelet and procoagulant hemostatic links activation has been found. This process was accompanied by the activation of lipid peroxidation and decreased antioxidant activity of the blood, which in turn led to increased permeability of blood vessels of pregnant women with preeclampsia.